A conflict between China and Taiwan: An analysis from a realism perspective - Halda Nuriyya Azzara; Badrus Sholeh (Journal of Social Studies (JSS), 2022)
The conflict between China and Taiwan has become a long conflict that until now has not found a bright spot. From time to time, the conflict between China and Taiwan seems to be getting worse and always attracts the attention of the international community. The dispute between the two countries also affects relations between countries, whether dealing with China or Taiwan. This article will analyze the conflict between China and Taiwan from the perspective of realism as a theory in the study of international relations. By analyzing the conflict from the perspective of realism, this article will discuss how China and Taiwan try to maintain their national integrity and how other countries interact with this conflict. The research method used in this article is literary studies by collecting secondary data to explain and analyze the conflict and find the result and discussion. By this method, there are some points were found, starting from the concept of power in the conflict between China and Taiwan, the diplomatic relations, and the survival of both parties in the international system.